High-performance road network assessment equipment - Barrantes Jiménez, Roy (2025)
n order to answer to the express need to establish procedures capable of offering support to the eventual creation of a Pavement Management System in Costa Rica, the Evaluation of the National Road Network Unit (LanammeUCR) developed a series of methodologies with the use of high performance equipments. With these methodologies it was possible to establish a systematic evaluation process and technical objective criteria to realize an evaluation of the functional and the structural capacity, skid resistance and the level of superficial deterioration for the whole National Road Network. Once implemented these methodologies it was possible to generate and maintained a database with detailed information of the general condition of the road network, which could be use as a technical base for the generation of investment plans and intervention strategies.